Biosensors: 10th Anniversary Feature Papers - Rocha-Santos, Teresa A. P.; da Costa, João P. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Biosensors are analytical devices used for the detection of a chemical substance, or analyte, which combines a biological component with a physicochemical detector. Detection and quantification are based on the measurement of the biological interactions. The biological element of a biosensor may consist of tissues, microorganisms, organelles, cell receptors, enzymes, antibodies and nucleic acids. These devices have been shown to have a wide range of applications in a vast array of fields of research, including environmental monitoring, food analysis, drug detection and health and clinical assessment, and even security and safety. The current Special Issue, "Biosensors: 10th Anniversary Feature Papers", addresses the existing knowledge gaps and aids the advancement of biosensing applications, in the form of six peer-reviewed research and review papers, detailing the most recent and innovative developments of biosensors.